GEOFÍSICA APLICADA A LA EVALUACIÓN DE LA VULNERABILIDAD A LA CONTAMINACIÓN EN ZONAS RURALES - Claudia Mabel Sainato; Beatriz Norma Losinno; Griselda Galindo; Ana Maria Landini; Ana Maria Fazio (Revista Águas Subterrâneas, 2006)
Agricultural and cattle activities are considered to be the source of high risk of contamination of groundwater. The contamination is the result of the interaction between the contaminant charge and the aquifer vulnerability. The aim of this work was to evaluate the vulnerability of the Pampeano aquifer at some rural zones of the highly productive area of Pergamino-Arrecifes river basin. The traditional method of indexation was used taking into account the principal factors which influence: the depth of free groundwater level, the degree of confinement of the aquifer and the lithology of non saturated zone. The first one was obtained through geoelectrical prospecting, due to the lack of well information at some places. The last factors were estimated based on hidrogeological features known from some wells. The influence of the edaphic zone (soil) was incorporated as a new index by means of texture properties of soils sampled at each site and soil maps. Even if vulnerability was moderate for all the studied sites, some places along both margins of the Pergamino river had higher indexes than the surroundings of Arrecifes town. The small urban centers had greater risk of contamination of groundwater due to their intrinsic vulnerability (higher indexes) and the potential contaminant charge that intensive agricultural and cattle activities, which are developed around these sites, may generate. Higher values of nitrate concentrations were found at these places with a sharp increasing tendency during the last years, indicating the need of stronger control over the effect of these activities on groundwater contamination.